DEVELOPMENT OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Dwi Zulaikah, Retno (CV. Lafadz Jaya, 2024)
The corona virus has had a fairly broad impact on community activities, one of which is the impact on economic activities in banking financial institutions, both in conventional banks and Islamic banks. The type of research used is field research. This research is descriptive qualitative, which means it describes a research subject. The data analysis technique used in this study, the author uses qualitative descriptive analysis. The growth of Islamic Commercial Banks during the Covid-19 pandemic in 2020 decreased and began to recover in 2021. In the problematic financing component, there was a decrease in the risk of problems until 2021, due to more selective financing distribution. The results show that the DPK indicators, which include savings, current accounts and deposits, experienced a setback in 2020 and recovered again in 2021. Thus, it can be concluded that Sharia Commercial Banks are also faltering with the presence of the Corona outbreak that has hit the world, post-Covid-19 development of Sharia Commercial Banks began to slowly recover with increasingly improving performance.